UNDERSTANDING THE NEXUS BETWEEN ABUSIVE SUPERVISION, KNOWLEDGE HIDING BEHAVIOR, WORK DISENGAGEMENT, AND PERCEIVED ORGANIZATIONAL SUPPORT IN TOURISM AND HOSPITALITY INDUSTRY - Tarik Ali JASIM; Azza Abdel MONEIM; Sally Fathy EL-SAYED; Hazem Ahmed KHAIRY; Sameh FAYYAD (Geo Journal of Tourism and Geosites)
Supervisors' dispositions have not received enough attention as potential antecedents to employees' knowledge - hiding behaviors. Based on this, the current study investigates the impact of abusive supervision on knowledge-hiding behaviors, considering the mediating role of work disengagement in this relationship, as well as investigating the moderating role of perceived organizational support in the study model. Data was obtained from frontline service employees of five-star hotels in Sharm El-Sheikh and tourism companies in Cairo, Egypt, by a questionnaire that surveyed 298 employees. The collected data was scrutinized using the Smart PLS-structural equation modeling technique. The PLS-SEM statistics proved the highly positive and significant effect of abusive supervision on knowledge-hiding behavior and employees’ work disengagement, supported the mediating effect of work disengagement, and the moderating effect of perceived organizationa l support. The study highlights some practical implications for hotels, such as implementing integrated knowledge offering a digital library, continuous management and administrative skills training, and behavioral training to facilitate the gaining of knowledge and enhance staff skills, self-confidence, loyalty, and job security. It also strongly suggests adopting a strategy to monitor abusive supervisors through open communication channels, regularly conducting exit interviews to reduce turnover, and enhancing engagement, thereby preventing abusive practices.